Health Maintenance Deficits in a Fully Insured Population of Adolescents With Chronic Medical Conditions. (June 2017) - Sainato, Rebecca; Flores, Michelle; Malloy, Allison; Geaney, Casey; Rajnik, Michael; Ottolini, Martin; Weisse, Martin
The current national monitoring of routine wellness care and vaccine uptake does not provide data on health maintenance among pediatric populations with chronic medical conditions. In this case-control study that analyzes wellness visits and vaccine uptake among adolescents, ages 16 to 18 years, we identified 938 without (controls) and 74 with (cases) 1 of 12 specific chronic medical conditions. The PPSV23 (23-valent pneumococcal polysaccharide vaccine) is recommended by the Advisory Committee on Immunization Practices for these 12 conditions and served as a measure of uptake for medically indicated vaccines. Our controls were twice as likely as cases to have a documented well visit in the past year, and there was a significantly higher proportion of controls than cases vaccinated with Tdap (tetanus toxoid, reduced diphtheria toxoid, acellular pertussis), MCV-4 (quadrivalent meningococcal conjugate), and HPV (human papillomavirus), all P < .05. More than 60% of cases failed to receive PPSV23. Adolescents with chronic medical conditions are at high risk of neglecting routine health maintenance.